Excess heat capacity in liquid binary alkali-fluoride mixtures - Beilmann, Markus; Beneš, O.; Capelli, E.; Reuscher, V.; Konings, R. J. M.; Fanghänel, Thomas (Inorganic chemistry, 2013)
Using drop calorimetry, we measured enthalpy increments of the LiF-KF, LiF-RbF, and LiF-CsF binary systems at temperatures above the melting point. Ten samples with different compositions (four compositions for LiF-KF, one composition for LiF-RbF, and five compositions for LiF-CsF) were prepared and measured between 884 K and 1382 K. To protect the calorimeter from corrosive fluoride vapor at high temperature, an encapsulating technique developed for this purpose was used. The samples were filled in nickel containers that were sealed by laser welding and afterward used for the measurements. From the obtained results, we derived the molar heat capacity functions of the respective samples. The heat capacities of the samples, having different compositions of the same binary system, were compared with the values for ideal behavior and the excess heat capacity function was determined for the entire composition range of the liquid solution. It was found that the excess heat capacities clearly depend on the cation radius and increase in the following order: LiF-NaF < LiF-KF < LiF-RbF < LiF-CsF.
Gesehen am 20.11.2020